2010
DOI: 10.1007/s10029-010-0683-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors related with unfavorable outcomes in groin hernia repairs

Abstract: The risk of complicated presentation and unfavorable outcome in patients with groin hernia is significant in the presence of factors such as advanced age, femoral hernia, female sex, delayed admission, severe coexisting cardiopulmonary problems and high ASA score. Although it is difficult to estimate the natural history of untreated hernia, hernia repairs of patients with the above-mentioned risk factors should be timely and elective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 16 publications
0
19
0
4
Order By: Relevance
“…It has been shown that watchful waiting is a safe and acceptable alternative for male patients with asymptomatic or minimally symptomatic inguinal hernias [10]. It would be ideal to identify patients within the asymptomatic/minimally symptomatic male group who would benefit from interventions, like smoking cessation, during their delayed repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that watchful waiting is a safe and acceptable alternative for male patients with asymptomatic or minimally symptomatic inguinal hernias [10]. It would be ideal to identify patients within the asymptomatic/minimally symptomatic male group who would benefit from interventions, like smoking cessation, during their delayed repair.…”
Section: Discussionmentioning
confidence: 99%
“…It would be ideal to identify patients within the asymptomatic/minimally symptomatic male group who would benefit from interventions, like smoking cessation, during their delayed repair. Risk factors such as advanced age, cardiopulmonary disease and high ASA score are known to adversely affect the outcomes of hernia repair [10]. Preoperative smoking has been associated with postoperative pneumonia [9].…”
Section: Discussionmentioning
confidence: 99%
“…Sonuç olarak eiektif onanmlarla karçilaçtirildigmda femoral herni ve dolayli olarak kadm cinsiyetin, acil inkarsere herni onanmlan için risk grubu oluçturdugu dücünülmektedir. Kasik fitiklarindaki risk faktörlerini analiz ettigimiz önceki bir çali §mamizda kadm cinsiyetin femoral herni, acil baçvuru, inkarserasyon ve strangülasyon için olumsuz bir faktör oldugunu bildirmiçtik ve kadm hastalarm kisa sürede eiektif olarak opere edilmesirü önermictik (20). Uyumlu olarak, bu çali §mamizda eiektif onarimlarla kar §ila §tirildigmda, kadm cinsiyet ve femoral hemide istatistiksel olarak anlam bulmanuza ragmen, olumsuz durumlarm incelenmesinde tek degijkenli istatistiksel analizde strangülasyon ve omentum-barsak rezeksiyonlari için herni tipi ve kadm cinsiyet anlamli farklilik düzeyine ula §mami §tir.…”
Section: Tartiçmaunclassified
“…Bunun yarunda bu etkisizlik mantiksal olarak rezeksiyondan daha çok hastarun yandaç hastalik birlikteligi ve yüksek ASA skorunun postoperatif lokal-sistemik komplikasyon ve uzun hastanede kali § süresine etkili olmasi ile açiklanabilir. Uyumlu olarak kasik fitiklarmda risk faktörlerini inceledigimiz önceki çaliçmamizda strangülasyon ve rezeksiyon oranlan yandaç hastahgi olanlarda yüksekti ve bu hastalarda hastanede kaliç süreleri belirgin olarak daha uzundu(20). Ote yandan, fiùklarda daha yüksek komplike bagvuru ve yandaç hastahgi olan ileri bir referans hastanesinde klinik düzenleme yollan ile giderleri ve hastanede kaliç sürelerini azaltmayi amaçlayan isviçre kaynakli bir çaliçmada gün olarak toplam ve postoperatif hastanede kaliç or-…”
unclassified
“…Nevertheless complications developed after emergency repairs may be more dramatic and frequent, even mortality may be recorded. 3,4 Especially, in the case of elderly population. 5,6 Hence, repair in an elective setting is generally recommended.There are also, few surgeons who adopt a wait and watch approach in slow, evolving, asymptomatic cases.…”
Section: Introductionmentioning
confidence: 99%